Improved Improved Early Childhood Balance Skills: Through Footboard Play and Shell Stretch - Khairani Faizah; Sumaryanti Sumaryanti; Sulistiyono Sulistiyono; Sumaryanto Sumaryanto; Guntur Guntur; Sigit Nugroho (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to identify: (1) the effect of play procedures on the increase in early childhood balancer, (2) the usefulness of the comparison of the effect between playing the footboard and shell stilts on the increase in early childhood balancing. This type of research is an experiment with the design of two groups pre-test and post-test. The population in this study was 100 children (PAUD) at Dharma Yoga Santi landfill. The sample in this study amounted to 72 children taken using purposive sampling criteria (1) certain children aged 5-6 years, (2) children who are active in school, (3) children are not sick, (4) male and female, (5) willing to follow the learning process (6) Able to follow all learning model programs that have been prepared, then divided into 2 groups. The instrument used to measure early childhood balancer is the Stork Stand Test. The information analysis method used is an independent sample t-test followed by a paired sample t-test. The results of the study proved that: 1) There was a significant influence of playing procedures on the increase in balancing by obtaining a significance value smaller than 0.05 (p <0.05). 2) There is a significant comparison of the influence between the boardwalk playing group and the shell stretching group on the increase in balancer, it was tested that the average balancing value in the boardwalk group was 86.94 while the average value in the bat sling group was 64.67 with an average difference in post-test of 22.27. With this, it can be concluded that the group given the treatment of playing the boardwalk has greater usefulness than the group playing shell stilts.